Low viscosity alkyd resins based on trimethylolpropane and Peruvian oil - Obregón D. (2021)
The high-unsaturated fatty acid content of Sacha inchi oil (SIO), a perennial plant originally from Peru, has turned it into a potential raw material for the production of alkyd resins. In this study, different proportions of multifunctional polyols were used to prepare air-drying resins. Physicochemical characteristics (acid value, viscosity, colour, density, drying time, and hardness) of alkyds were evaluated. Moreover, FT-IR, TG–DTA, 1H-NMR and 13C-NMR characterization techniques were used. SIO-based alkyd resins prepared with trimethylolpropane exhibited low viscosities, suitable for preparing more manageable high solids protective coatings. © 2021, The Polymer Society, Taipei.